Ekonomi Biru dan Ketahanan Pangan: Studi Empiris Provinsi Kepulauan di Indonesia - Andaiyani, Sri; Marwa, Taufiq; Nurhaliza, Syella (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2024)
The food security issue has gained more attention recently by the food crisis during the Covid-19 pandemic. In the future, blue economy strategy will be crucial for Indonesia as an archipelagic country that has enormous potential in the marine and fisheries sector. This study aims to investigate the effect of the blue economy on food security in archipelagic provinces in Indonesia for the 2018–2022 period. The panel data regression with Ordinary Least Square (OLS) method is employed. The results show that blue economy has a positive and significant effect on food security. Therefore, the government needs to support the development of the blue economy with appropriate regulations and supervision. The diversification of food sources needs to be strengthened to reduce dependence on imported food. Finally, it is necessary to implement a holistic and integrated food policy involving various stakeholders.Abstrak Isu ketahanan pangan makin penting akhir-akhir ini, terutama pasca pandemi Covid-19. Konsep ekonomi biru dapat menjadi strategi yang penting, khususnya bagi Indonesia sebagai negara kepulauan yang memiliki potensi di bidang kelautan dan perikanan, untuk mendukung ketahanan pangan pada masa depan. Penelitian ini bertujuan untuk mengetahui pengaruh ekonomi biru terhadap ketahanan pangan di provinsi kepulauan di Indonesia pada periode 2018–2022. Metode yang digunakan adalah regresi data panel dengan Ordinary Least Square (OLS). Hasil penelitian menunjukkan bahwa ekonomi biru berpengaruh positif dan signifikan terhadap ketahanan pangan. Pemerintah perlu menyusun regulasi yang mendukung pengembangan dan pengawasan ekonomi biru. Diversifikasi sumber pangan perlu diperkuat untuk mengurangi ketergantungan terhadappangan impor. Selain itu, perlu diterapkan kebijakan pangan yang holistik dan terpadu dengan melibatkan berbagai pemangku kepentingan.